Reformulating New Student Admission Policy for SDG 4: A Local Values-Based Approach in Elementary Schools and Islamic Madrasahs in Gresik Regency - Nur Hamidah; Mustaji Mustaji; Bambang Sigit Widodo (Journal of Current Studies in SDGs, 2026)
Objective: To explore opportunities and challenges in implementing the New Student Admission Policy (PPDB) at elementary schools and Islamic elementary madrasahs (MI) in Gresik Regency, East Java, Indonesia. It examines how local education authorities manage national regulations while considering social, cultural, and geographical contexts. Method: A qualitative approach was employed, collecting data through interviews with stakeholders from selected SD and MI under the Gresik Regency Education Office and Ministry of Religious Affairs. Observations and document analyses supplemented the data, which were interpreted using relevant policy concepts and regulations to understand local implementation practices. Results: Successful PPDB implementation depends on local actors’ ability to navigate complex social and administrative demands. Flexible, culturally adapted policies promote equitable access, relevant educational outcomes, and high-quality services. Effective implementation requires cross-institutional coordination, strong social networks, and active community participation. Zoning systems and affirmative policies are essential to prevent exclusion and ensure schools in low-attractiveness areas receive adequate support. Novelty: The research offers a novel contribution by reformulating the implementation of the New Student Admission Policy (PPDB) beyond technical and administrative procedures through the integration of local values, socio-cultural contexts, and community needs. Unlike previous studies that primarily focus on policy compliance and operational aspects, this study demonstrates how context-sensitive policy implementation can strengthen equitable and inclusive access to basic education while advancing Sustainable Development Goal 4 (Quality Education), particularly Targets 4.1 and 4.5.